On the Margins of Consciousness Sketches for a Phenomenology of Digitized Attention - Vidali, Cristiano (Scenari, 2021)
In the vast panorama of digital studies, numerous works have investigated the cognitive consequences of digital devices on attention. In the present paper we will examine two among the best-known empirical studies on digitized attention in assiduous media users, aiming to cope with this issue in terms of a qualitative modification. We will then try to argue that the authors of such articles end up contravening their intentions, providing results that – as a natural consequence of their conceptual premises – ultimately seem to understand digital users’ distraction as a lack of attention. In this regard, we will briefly retrace Paul Sven Arvidson’s phenomenological account of attention and distraction, suggesting its potential role in reinterpreting the previous experimental findings. We will thus mean to outline a case study in which phenomenology and empirical sciences can prove a concrete and fruitful interaction.